2015
DOI: 10.1089/sur.2014.186
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of99mTc-Labeled Ceftizoxime in the Diagnosis of Subclinical Infections Associated with Titanium Implants in Rats

Abstract: (99m)Tc-ceftizoxime scintigraphy can localize preferentially periprosthetic-infected areas adjacent to metal implants in a murine model. Furthermore, the radiolabeled antibiotic appears to be capable of detecting alterations in the micro-environment close to the implant and of reaching the bacteria attached to the implant surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
(26 reference statements)
1
12
0
1
Order By: Relevance
“…It was found that our radiochemical complex in aqueous phase was detected at R.f = 1 as 98.8% pure while in previous published study it was 92%. As compared to previous published study, our synthesized radio complex was hydrophilic, showed mild retention of activity in liver and lungs and excreted through kidney. In vivo distribution of synthesized complex was compared with the unlabeled ceftizoxime published in research article and it was found that it followed the same path of distribution as unlabeled ceftizoxime…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…It was found that our radiochemical complex in aqueous phase was detected at R.f = 1 as 98.8% pure while in previous published study it was 92%. As compared to previous published study, our synthesized radio complex was hydrophilic, showed mild retention of activity in liver and lungs and excreted through kidney. In vivo distribution of synthesized complex was compared with the unlabeled ceftizoxime published in research article and it was found that it followed the same path of distribution as unlabeled ceftizoxime…”
Section: Discussionmentioning
confidence: 51%
“…Radio labelled antibiotics can serve effectively in this stance . 99m Tc labelled antibiotics like ciprofloxacin (Infecton) has been used in a number of human studies like bone infection with variable results and in diabetic foot infection and some animal studies of 99m Tc ceftizoxime by other group, except 99m Tc‐UBI (29‐41) peptide…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we used a third-generation cephalosporin as the radiopharmaceutical that is active against gram-positive, gram-negative, and anaerobic bacteria. Moreover, its application as a radiopharmaceutical has shown to be effective for soft tissue infections, osteomyelitis, and prosthetic infections 10,11,12,14,15 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…2018;33(1): [14][15][16][17][18][19][20][21] polyvinylpyrrolidone-iodine (Riodine ® ) in an antiseptic solution, followed by an alcoholbased solution, and protection with sterile fields. A longitudinal incision was formed at the thigh, dissecting the layers to expose the posterior diaphyseal region of the femur.…”
mentioning
confidence: 99%
“…Also Teixeira et al [86] used 99m Tc-ceftizoxime for the diagnosis of suspected infections in titanium implants in rat model. Control rats received a sterile implant, while experimental group received an implant infected with 10 9 CFU of S. aureus .…”
Section: Cephalosporinsmentioning
confidence: 99%